Tendency to depressive states, anxiety and strategies of coping behavior for boys and girls - E. F. Yashchenko; N. B. Kaznacheeva; E. V. Bazhanova (Вестник университета)
The article provides an overview of the study of the depressive states, anxiety and copying strategies issues in the Russian modern research literature. The purpose of the work is to determine the tendency to depressive states, anxiety and copying strategies among male and female students of various universities in St. Petersburg in the amount of 101 people, 50 of them boys and 51 girls aged 17–24 years. The following research methods are used: Zung Self-Rating Depression Scale in T.I. Balashova’s adaptation, Spielberger State-Trait Anxiety Inventory for identifying personal and situational anxiety in Yu.L. Khanin adaptation, The Lazarus coping test in T.L. Kryukova’s and E.V. Kuftyak’s adaptation. Statistical methods for processing empirical data include descriptive statistics by group, Mann–Whitney U test, correlation analysis, factor analysis. The authors present a general characteristic of students in terms of the studied phenomena. The researchers found differences between search for social support, flight-avoidance, positive reassessment, situational anxiety indicators in boys and girls with greater severity of average values in girls. Correlation analysis revealed both common and distinct relationships for male and female students. The following factors were identified using factor analysis: “Predictors of personal anxiety and tendency to depression,” “Constructive strategies for coping with difficult situations,” “Confrontation against situational anxiety,” characterizing features of students’ coping with depression and anxiety.